2020
DOI: 10.22541/au.159355985.50556448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engaging online students by activating ecological knowledge

Abstract: The current COVID-19 pandemic has forced the global higher education community to rapidly adapt to partially-or fully-online course offerings. For field-or lab-based courses in ecological curricula, this presents unique challenges. Fortunately, a diverse set of active learning techniques exist, and these techniques translate well to online settings. However, limited guidance and resources exist for developing, implementing, and evaluating active learning assignments that fulfil specific objectives of ecologyfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…I hope the activities and approaches described in this paper serve as a useful model for instructors of undergraduate ecology courses (especially those at urban university campuses) and add to existing suggestions for activating students’ ecological knowledge even during online instruction (Hines et al, 2020). I believe the factors that contributed to the success of this online course and the high level of student engagement—namely emphasizing applied urban ecology, a sense of place, and problem‐based learning—can add to the value of face‐to‐face CUREs for student learning.…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 95%
See 1 more Smart Citation
“…I hope the activities and approaches described in this paper serve as a useful model for instructors of undergraduate ecology courses (especially those at urban university campuses) and add to existing suggestions for activating students’ ecological knowledge even during online instruction (Hines et al, 2020). I believe the factors that contributed to the success of this online course and the high level of student engagement—namely emphasizing applied urban ecology, a sense of place, and problem‐based learning—can add to the value of face‐to‐face CUREs for student learning.…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 95%
“…Enhancing the accessibility of authentic research experiences should therefore be prioritized by educators in the field, especially in light of (and in spite of) the unique challenges imposed by remote learning; many undergraduates have completely missed out on in‐person laboratory courses and research activities since spring 2020. A number of creative solutions and strategies have been proposed for transitioning lab‐based ecology education online (Creech & Shriner, 2020; Harris et al, 2020; Hines et al, 2020; Lashley et al, 2020; Richter et al, 2021). I believe the lessons learned through teaching this class can inform effective teaching strategies in ecology online and once students and instructors return to the classroom, specifically the value of cultivating a sense of place, emphasizing applied ecology and problem‐based learning, and teaching across cultural strengths in ecology classes at urban university campuses.…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 99%
“…Authors contributed on topics related to how the pandemic affected students and instructors (e.g., Barton, 2020) and affected the utility of citizens science (e.g., Smith & Hamed, 2020). Authors contributed thoughtful and creative ways to use the pandemic to stimulate interest in ecology and evolution for students (e.g., Hsu, 2020), providing guidelines, insights, and instructions to safely maintain experiential or active learning or teach topics not well‐suited to online delivery (e.g., Acevedo, 2020; Creech & Shriner, 2020; Hines et al., 2020; Lashley & McCleery, 2020), contributions highlighting sources of inequity and strategies to be more inclusive in online delivery (e.g., Brandt et al., 2020), and ideas for use of tools, apps, and novel media to enhance engagement (e.g., Holt et al., 2020; Strickland et al., 2020). The COVID‐19 crisis demanded action, and with over 40 submissions to this special issue by our community, you have risen to the occasion.…”
Section: The Goals Of This Special Issuementioning
confidence: 99%
“…Previous research has found that based on survey results from 186 colleges, students engaged successfully when learning activities involve students with materials, educators, and other students [8]. The type of learning media may influence students' perceptions of their engagement level [9]. One of the popular media that can increase student participation is mobile-based learning.…”
Section: Introductionmentioning
confidence: 99%